Geochemical Analysis of Calcareous Shale of Baong Formation (North Sumatera Basin) as Potential Source Rock - Alfian, Zika; Sartika, Dewi; Rifqan, Rifqan; Muhni, Akmal; Adrian, Fahri; Putra, Hidayat Syah (Graduate School of Universitas Syiah Kuala, 2024)
This research is related to calcareous shale whose samples were obtained from surface data (outcrop). This rock outcrop is characterized as a rock rich in organic material and impermeable, so it is predicted to become a source rock of oil and gas petroleum system. The amount of organic content or carbon material and the level of maturity of the rock is a benchmark for determining whether or not it is appropriate to be called a source rock of the petroleum system in the North Sumatra Basin (NSB) area. The method used in the present study is the rock-eval pyrolysis method and the determination of Total Organic Carbon is carried out through laboratory testing. Based on the results of Rock-Eval Pyrolysis testing, the maturity level or Tmax of the rock is 446-degree Celsius which indicates the peak mature category with kerogen type in the form of II/III which tends to produce oil and gas prone. The results of the Total Organic Carbon (TOC) test show a value of 1.26% which is included in the category of organic matter richness in the good category. Based on the results of these two tests, it can be concluded that the Calcareous shale found in the North Sumatra Basin (NSB) can be categorized as a good Source Rock with a Peak Mature maturity level and has the potential to produce Oil and Gas (Mixed oil and gases).